Organocatalytic Enantioselective Aza‐Michael Reaction of Benzotriazole to β, β‐Disubstituted Nitroalkenes. Issue 13 (18th June 2015) - Chen, Sheng‐Wei; Zhang, Gui‐Cheng; Lou, Qin‐Xin; Cui, Wei; Zhang, Sha‐Sha; Hu, Wen‐Hui; Zhao, Jun‐Ling
Abstract An enantioselective aza‐Michael reaction of benzotriazole to β, β‐disubstituted nitroalkenes has been developed. This reaction was catalyzed efficiently by a bifunctional thiourea catalyst, affording the corresponding products, bearing quaternary stereogenic centers, in moderate to high yields (up to 80 %) and with high enantioselectivities of up to 95 % ee.